2010
DOI: 10.1039/c0nr00345j
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized gold nanoparticles: a detailed in vivo multimodal microscopic brain distribution study

Abstract: In the present study, the in vivo distribution of polyelectrolyte multilayer coated gold nanoparticles is shown, starting from the living animal down to cellular level. The coating was designed with functional moieties to serve as a potential nano drug for prion disease. With near infrared time-domain imaging we followed the biodistribution in mice up to 7 days after intravenous injection of the nanoparticles. The peak concentration in the head of mice was detected between 19 and 24 h. The precise particle dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 30 publications
0
75
0
Order By: Relevance
“…However, other studies on the effects of nanoparticles, have reported that other kinds of nanoparticles (like gold nanoparticles) injected into the tail vein of healthy mice show a biodistribution in the brain, and this has been characterized in detail. 15 One other study exposing rats to ZnO given daily (100 mg) via a gastric tube, showed morphological and histochemical changes in the brains of rats. 16 Based on these data, we assumed that nano-ZnO given intraperitoneally can cross the BBB and have influence on the brain.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…However, other studies on the effects of nanoparticles, have reported that other kinds of nanoparticles (like gold nanoparticles) injected into the tail vein of healthy mice show a biodistribution in the brain, and this has been characterized in detail. 15 One other study exposing rats to ZnO given daily (100 mg) via a gastric tube, showed morphological and histochemical changes in the brains of rats. 16 Based on these data, we assumed that nano-ZnO given intraperitoneally can cross the BBB and have influence on the brain.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…For example, compared with hydrophobic NPs, hydrophilic nanocrystalline TiO 2 NPs exhibit a greater influence on the 5-HT and 5-HIAA monoamine levels in the subbrain regions. 137 Sousa et al 138 modified the 15 nm gold NP surface by coating with functional polyelectrolyte layers and human serum albumin and found that the modified gold NPs were able to pass the BBB and accumulate in neuronal or glial cells in specific regions close to the brain stem.…”
Section: Surface Modificationmentioning
confidence: 99%
“…The particles were investigated for their ability to cross the blood brain barrier by intravenous injection into mice. Ex vivo CT scans of the brain showed the highest CT signal was located at the thalamus and hypothalamus [105].…”
Section: Passively Targeted Gold Nanoparticle Formulationsmentioning
confidence: 99%